Manajemen Pendidikan Karakter di Madrasah Bertaraf Internasional Amanatul Ummah Pacet Mojokerto - Hendra Rizki Rangkuti (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
Globalization besides bringing positive impacts and also negative impacts. Parents of students complain about their child's unmanageable behavior. Therefore, the school has the duty and responsibility to continue the basic education given in the family. Because of the importance of this responsibility, schools need to have good planning, implementation and evaluation related to character education. This research uses a qualitative approach with a case study type of research. Data sources were obtained from MBI and representatives. While collecting data through interviews, observation, documentation. From the results of the study it was concluded 1) Planning for character education is a) Grand idea which includes vision, mission, foundation, Madrasah commitment, 7 keys to student success and future goals of students, B) Pre-work meeting, c) work meeting. 2) Implementation of character education is a) Development of new students B) Talent Development and Development Program C) Student organization development program D) Development Program E) Madrasah annual agenda F) Implementation of the Muis curriculum program g) Implementation of the Islamic Boarding School program 3) Evaluation of character education consists of a) evaluations take place on the spot b) direct evaluations by teachers in Class C) weekly evaluations conducted by officials and homeroom teachers. d) monthly evaluation e) annual evaluation f) evaluation based on input, criticism, and suggestions.